Research and extension action for parasitic control in pig breeding families located in Tanguá, Rio de Janeiro - Camila S.C. Class; Renato L. Silveira; João Pedro S. Palmer; Priscila A. Fialho; Lucas F. Lobão; Laís V. Dib; Claudia Maria A. Uchôa; Alynne S. Barbosa (Pesquisa Veterinária Brasileira)
ABSTRACT: This study aimed to analyze the parasites infesting pigs and their producers on family farms in Tanguá, RJ, Brazil, and to conduct extension activities between 2018 and 2019. Fecal samples were collected from 132 pigs, as well as, skin scrapings from the ears of 125 animals. In addition, 36 stool specimens from farmers and their families were analyzed. The collected material was processed by direct examination, sedimentation and flotation techniques. Gastrointestinal parasites were detected in 88.6% of the pigs, especially coccidia (71.8%), Balantioides coli (55%), strongyles (40.2%) and Strongyloides ransomi (31.6%) which showed statistically significance (p<0.05). Ectoparasites were identified in 16% of the pigs, mostly Sarcoptes scabiei var. suis (76.2%). Parasites were detected in 19.4% of the humans, including, Entamoeba coli (19.4%), Ascaris lumbricoides (8.3%) and Trichuris trichiura (5.5%). The frequency of B. coli and S. scabiei var. suis (p<0.05) were statistically significant, when analyzing the age group of the animals, having been more detected in the older years, fatterners phase. The pig farmers participated in these activities extension, which included lecture and “field day”, aimed at imparting information about parasites and their prophylaxis. The situation in Tanguá pig farms reinforces the need to carry out programs that provide technical support to these farmers, whose livelihood depends on pig farming.